Complex approach to the conservative treatment of hallux rigidus - D. V. Ilchenko; D. O. Ilyin; A. A. Kardanov; E. E. Achkasov; A. V. Korolev (Научно-практическая ревматология)
Introduction. Hallux rigidus (HR) is a common source of forefoot pain, which leads to progressive loss of range of motion in the first metatarsophalangeal (MTP1) joint and pathologically affects biomechanics of the whole lower limb. HR is characterized by degeneration of the articular surfaces of MTP1 joint with the formation of bone growths, cysts and erosions, osteochondral defects and loose bodies. The frequency of occurrence of HR is 1 in 40 adults older than 50 years, and this localization of osteoarthritis is the most common among all joints of the foot. The aim of this article is to improve the results of conservative treatment of HR through the use of physical rehabilitation methods, such as manual therapy, therapeutic exercises and foot orthotics.Materials and methods. This study included retrospective cases of 24 patients (28 feet), who underwent a single course of conservative treatment of HR at the European Clinic for Sports Traumatology and Orthopedics (ECSTO) of the European Medical Center (EMC) since January 2014 to December 2018. The patients’ mean age was 51 years (range, 41 to 69 years). Median time between the beginning of treatment and final examination was 26 months (interquartile range from 17 to 36 months). Patient satisfaction, VAS pain scale, AOFAS and FAAM questionnaires and MTP1 dorsiflexion were evaluated in this study.Results. According to AOFAS scale, we obtained 18% (5/28) of excellent, 78% (22/28) of good, 4% (1/28) of fair and no poor results. Median AOFAS score significantly increased from 58.5 points before treatment to 87.0 points on the final examination (p<0.05). Median FAAM daily activity subscale showed 98% of functional outcome with median subjective score of 95%, median FAAM sports score was 97% and median subjective sports score rate was 90%. Patient’s satisfaction at the final examination was “excellent” in 57% (16/28), “good” in 39% (11/28), “fair” in 4% (1/28) of cases and no poor results were obtained. Median VAS pain scale decreased from 5 points before treatment to 1 point at the final examination (p<0.05). Median angle of the MTP1 dorsiflexion significantly increased from 23° before treatment to 30° on the final examination (p<0.05).Conclusion. Described approach of the conservative treatment of HR is an effective method of treatment of early stages of the disease with high patient satisfaction rate and functional outcome.